(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To determine the proportion of colorectal cancer patients undergoing chemotherapy whose dietary intake meets the recommended requirements for energy, macronutrients, and vitamins at Ho Chi Minh city Oncology Hospital. Participants and methods: A descriptive cross-sectional study was conducted at Ho Chi Minh city Oncology Hospital from October 2022 to April 2023 on 210 colorectal cancer patients undergoing chemotherapy. Data were collected from medical records and face-to-face patient interviews using a general information questionnaire and 24-hour dietary intake interview questions. Stata software was used to analyze data, and Vietnam Eiyokun was used to calculate the nutritional composition of patients’ diets. Results: The study population had a mean age of 57.3 ± 11.9 years, with males accounting for 49.5%, and 83.8% of patients were in stages III-IV. The proportion of colorectal cancer patients whose dietary intake met the recommended energy requirement was 35.7%. The adequacy rates were 44.3% for protein, 66.2% for lipid, and 57.1% for carbohydrate. Among vitamins, vitamin B1 had the highest adequacy rate (47.5%), followed by vitamin C (29.1%), vitamin PP (21%), and vitamin A had the lowest (9.5%). Regarding minerals, 41.5% met the recommended intake for iron, while only 11% met the recommendation for calcium. Notably, only 0.5% of patients had a fiber intake that met the recommended level. Conclusion: Colorectal cancer patients undergoing chemotherapy had a low rate of meeting the recommended dietary intake for energy, macronutrients, vitamins, minerals, and fibre. Therefore, timely nutritional counseling and interventions are necessary to improve the overall dietary status of these patients.